Separador de polarización integrado de altas prestaciones basado en estructuras sub-longitud de onda - Luque-González, José Manuel; Herrero-Bermello, Alaine; Ortega-Moñux, Alejandro; Sánchez-Rodriguez, Marina; Velasco, Aitor V.; Schmid, Jens H.; Cheben, Pavel; Molina-Fernández, Íñigo; Halir, Robert (My University, 2020)
Polarization management is a key factor in photonics integration platforms with high birefringence such as Silicon-On- Insulator. Here we design a directional coupler polarization beam splitter composed of two subwavelength waveguides, which only differ in the tilt angle of the silicon segments. Our simulations predict an extinction ratio higher than 20 dB over an 86 nm bandwidth with negligible losses. The fabricated device is only 14 μm long, covers a 72 nm bandwidth with sub-decibel insertion losses and exhibits an extinction ratio in excess of 15 dB.
Keywords: Circuitos integrados-Diseño y construcción; Fotónica; Silicio sobre aislante; Sistemas de comunicación inalámbricos; Polarización; Microelectrónica-Materiales; Polarization management; SWG; Photonics; SOI; Birrefringencia